Molecular phylogenetics of stream treefrogs of the Hyloscirtus larinopygion group (Anura: Hylidae), and description of two new species from Ecuador - Coloma, Luis A.; Carvajal-Endara, Sofía; Dueñas, Juan F.; Paredes-Recalde, Arturo; Morales-Mite, Manuel; Almeida-Reinoso, Diego; Tapia, Elicio E.; Hutter, Carl R.; Toral, Eduardo; Guayasamin, Juan M. (Zootaxa, 2012)
We review the systematics of frogs of the Hyloscirtus larinopygion group. A new phylogenetic tree inferred frommitochondrial DNA (partial sequences of 12S rRNA, valine-tRNA, and 16S rRNA genes; 2.3 kb) of eleven species ofthe H. larinopygion group is provided, based on maximum parsimony, maximum likelihood, and Bayesian analyses. Ourphylogeny confirms the close relationship of members of the H. larinopygion group with Andean relatives of the H.armatus group, which also occurs in the Andes. Hyloscirtus tapichalaca is placed as sister species to the rest of the H.larinopygion group, in which two clades (A+B) are evident. Although ingroup relationships are well supported, themonophyly of the H. larinopygion group and placement of H. tapichalaca require additional testing. Genetic divergencesamong species of the H. larinopygion group are shallow compared to those observed in many other anurans, with geneticdistance among sister species (H. princecharlesi and H. ptychodactylus) as low as 1.31%. However, this pattern isconcordant with radiations in other highland Andean lineages of anurans that show marked morphological or behavioraldifferentiation, but low divergence in mitochondrial markers. Divergence-time analyses (using BEAST) indicate that theHyloscirtus clade is a relatively ancient lineage that appeared in the Eocene, at a minimum age of 51.2 million years ago(MYA), while the H. larinopygion group originated in the Middle-Late Eocene at a minimum age of 40.9 MYA. Ourresults might suggest a rapid radiation of Hyloscirtus starting in the Miocene into the Pliocene, from at least 14.2 MYA tothe most recent divergence between sister taxa at 2.6 MYA. We also describe two sympatric new species of Hyloscirtusfrom northwestern Ecuador: H. criptico sp. nov. and H. princecharlesi sp. nov. We diagnose them by their phylogeneticposition (they are not sister to each other), genetic divergence, and a unique combination of color patterns, and othermorphological features. Additionally, we describe the suctorial tadpoles and the extreme ontogenic color changes in H.larinopygion, H. lindae, H. pantostictus, H. princecharlesi, H. psarolaimus, and H. tigrinus. Furthermore, we describe theosteology of H. criptico, H. lindae, H. pacha, H. pantostictus, H. princecharlesi, H. psarolaimus, H. ptychodactylus, andH. staufferorum. We describe vocalizations of H. lindae, H. pacha, H. pantostictus, H. pasarolaimus, H. staufferorum, andH. tapichalaca. Hyloscirtus tigrinus is recorded for the first time in Ecuador and its range is extended 62.4 km (airlinedistance), from its southernmost locality record in Departamento de Nariño, Colombia. Most species of the H.larinopygion group are currently severely threatened by extinction, after surviving the catastrophic extinctions in the1980s and 1990s that led to the disappearance of many other sympatric anurans that bred in swiftly flowing water and hadlotic water tadpoles in the Andean highlands. Research and conservation actions are urgently needed for these species. Inorder to better call attention to these conservation issues, we name one of the new species in honor of Prince Charles ofWales, who is contributing significantly to the growth of awareness in the battle against tropical deforestation, climate change, and the catastrophic extinction of rainforest amphibians.